Grace and gigabytes : being church in a tech-shaped culture - Panzer, Ryan M. (Fortress Press, 2020)
Grace and Gigabytes explores the intersection of technology, culture, and church. Examining digital technology not as a set of tools, but as a force for cultural transformation, Ryan M. Panzer explores the networked values of the digital age--questions, connection, collaboration, and creativity; demonstrates the need for the church to change if it is to realize its mission; and makes recommendations for the practice of ministry today.